High rate of discontinuation may diminish PrEP coverage among young men who have sex with men - Morgan, Ethan (AIDS Behav, 2018)
Understanding PrEP discontinuation is key to maximizing its effectiveness at the individual and population levels. Data came from the RADAR cohort study of MSM aged 16–29 years, 2015–2017. Participants included those who reported past six-month PrEP use and discontinued its use by the interview date. Of the 197 participants who had used PrEP in the past six months, 65 discontinued use. Primary reasons for PrEP discontinuation included trouble getting to doctor’s appointments (14, 21.5%) and issues related to insurance coverage or loss (13, 20.0%). Few (21%) who discontinued spoke to their doctor first, which has important implications for future long acting formulations.